MAJOR FLAWS IN TECHNIQUE OF INTRAMUSCULAR INJECTIONS: Technique of Intramuscular Injections - Waleem, Maj Sheikh Saadat Ullah; Khan, Yasser Saeed; Tarar, Humayun Munir (Pakistan Armed Forces Medical Journal, 2013)
Objectives: To identify the major flaws in technique of administering intramuscular injections by our health care professionals and to suggest improvements based upon a scientific study.Design: Cross sectional (Jan-Feb, 2011).Place: Combined Military Hospital Sargodha, Pakistan Air Force Hospital Sargodha, Pakistan Air Force Hospital Mianwali.Patients and Methods: All staff involved in administration of IM injection to the patients. A detailed questionnaire was required to be filled in front of an observer and submitted. Injection sites were required to be marked on diagrams. The data were analyzed by SPSS 17.Results: Major flaws were identified in the technique of administration of IMI.